Selective photodynamic effects on cervical adenocarcinoma cells provided by F127 Pluronic®-based micelles modulating hypericin delivery - Kayane Harumi Mashiba; Lucimara Rofrigues Carobeli; Maria Vítoria Felipe de Souza; Lyvia Eloiza de Freitas Meirelles; Natália Lourenço Mari; Gabriel Batista César; Renato Sonchini Gonçalves; Wilker Caetano; Edilson Damke; Vânia Ramos Sela da Silva; Gabrielle Marconi Zago Ferreira Damke; Marcia Edilaine Lopes Consolaro (Universidade de São Paulo, 2023)
Abstract Cervical cancer is a leading cause of death among women. The endocervical adenocarcinoma (ECA) represents an aggressive and metastatic type of cancer with no effective treatment options currently available. We evaluated the antitumoral and anti-migratory effects of hypericin (HYP) encapsulated on Pluronic F127 (F127/HYP) photodynamic therapy (PDT) against a human cell line derived from invasive cervical adenocarcinoma (HeLa) compared to a human epithelial cell line (HaCaT). The phototoxicity and cytotoxicity of F127/HYP were evaluated by the following assays: colorimetric assay, MTT, cellular morphological changes by microscopy and long-term cytotoxicity by clonogenic assay. In addition, we performed fluorescence microscopy to analyze cell uptake and subcellular distribution of F127/HYP, cell death pathway and reactive oxygen species (ROS) production. The PDT mechanism was determined with sodium azide and D-mannitol and cell migration by wound-healing assay. The treatment with F127/HYP promoted a phototoxic result in the HeLa cells in a dose-dependent and selective form. Internalization of F127/HYP was observed mainly in the mitochondria, causing cell death by necrosis and ROS production especially by the type II PDT mechanism. Furthermore, F127/HYP reduced the long-term proliferation and migration capacity of HeLa cells. Overall, our results indicate a potentially application of F127/HYP micelles as a novel approach for PDT with HYP delivery to more specifically treat ECA.